Molecular basis for integrin adhesion receptor binding to p21-activated kinase 4 (PAK4) - Ha, Byung Hak; Yigit, Sezin; Natarajan, Nalini; Morse, Elizabeth M.; Calderwood, David A.; Boggon, Titus J. (Communications biology, 2022)
Integrin adhesion receptors provide links between extracellular ligands and cytoplasmic signaling. Multiple kinases have been found to directly engage with integrin β tails, but the molecular basis for these interactions remain unknown. Here, we assess the interaction between the kinase domain of p21-activated kinase 4 (PAK4) and the cytoplasmic tail of integrin β5. We determine three crystal structures of PAK4-β5 integrin complexes and identify the PAK-binding site. This is a region in the membrane-proximal half of the β5 tail and confirmed by site-directed mutagenesis. The β5 tail engages the kinase substrate-binding groove and positions the non-phosphorylatable integrin residue Glu767 at the phosphoacceptor site. Consistent with this, integrin β5 is poorly phosphorylated by PAK4, and in keeping with its ability to occlude the substrate-binding site, weakly inhibits kinase activity. These findings demonstrate the molecular basis for β5 integrin-PAK4 interactions but suggest modifications in understanding the potential cellular role of this interaction. Crystal structures of integrin β5 tails with PAK4 reveal a unique interaction in which integrin β5 is not phosphorylated by PAK4 but rather inhibits PAK4 activity.